Enchanted Calvinism : labor migration, afflicting spirits, and Christian therapy in the Presbyterian Church of Ghana /: labor migration, afflicting spirits, and Christian therapy in the Presbyterian Church of Ghana. (2013) - Mohr, Adam
No abstract available